The use of methods, where and how to use them. Methodological aspect. The concept of the reflective and expert teacher (British Journal of Multidisciplinary and Advanced Studies, 2023)
The methodological aspect is related to the importance of the study of didactics which is a main field of the science of pedagogy which studies the theoretical bases of the teaching process. Didactic thought is as old as pedagogical thought itself. Since that time, it has developed without interruption, where learning as well as education had its own specificity, whether in the theoretical, axiological or practical sense. Of particular importance and actuality are those that express the demands of the time in the field of teaching methods, such as the active acquisition of knowledge and its sustainability, the development of creative thinking and the education of independent work skills in pupils and students. The transmission and acquisition of a certain volume of knowledge in the form of concepts, laws, social phenomena, where on the basis of this selection and according to an advanced and contemporary conceptual apparatus, the didactic equivalents of scientific knowledge are determined.